Empowering Women’s Groups through IoT-Based Aeroponic Automation for Sustainable Agriculture on Limited Land in Sidoarjo - Dwi Nurherdiana, Silvana; Mustika Rizki, Agung; Aini Fauziyah, Nur; Rizki Ramadhani, Mohamad; Rahimah, Aliya; Dewi Prasasti Tungga Dewi, Kun (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: The decline of agricultural land in Sumokembangsri Village due to industrial expansion has reduced local food production. This program aimed to enhance the community’s capacity, particularly PKK women’s groups, in cultivating vegetables on limited land through IoT-based aeroponic automation. Contribution: This community engagement initiative contributes to strengthening women’s roles in smart agriculture, improving technological literacy, enhancing production and management competencies, and offering a scalable model of aeroponic-based smart farming for land-constrained areas. Method: The program was conducted for six months and involved 78 active participants. Activities included socialization, hands-on training, IoT-based aeroponic installation, mentoring, and evaluation. Knowledge and management skills were assessed using structured questionnaires, while data were analyzed with descriptive statistics to measure learning outcomes and program effectiveness. Results: Participants showed substantial improvement in technical and managerial competencies. Knowledge of aeroponic principles increased from 40% to 88.85%, while understanding of its impact on crop quality and yield rose from 38.49% to 87.69%. Management capabilities, including resource management, team coordination, and organizational governance, also improved, with average scores rising from 66–71% to 94–98%. Participants successfully operated IoT-based systems and demonstrated strong motivation for sustaining smart farming practices. Conclusion: The integration of IoT-based aeroponic automation with community-based empowerment effectively enhances agricultural productivity, strengthens local capacity, and supports sustainable food production. The program achieves its objective of empowering PKK groups through smart technology and provides a replicable model for similar semi-urban rural communities facing land limitations.